Association between chronic kidney disease and colorectal cancer: evidence from meta-analysis and Mendelian randomization - Shuyi Qian; Yuting Gong; Ying Chen (Discover Oncology)
Abstract Objective Observational studies have yielded inconsistent findings on the relationship between chronic kidney disease (CKD) and the risk of colorectal cancer (CRC). This research utilized a meta-analysis of cohort studies along with two-sample Mendelian randomization (MR) approaches to explore the causal impact of CKD on CRC. Methods A thorough search was performed across PubMed, Web of Science, Embase, and the Cochrane Library, encompassing all relevant studies from their inception until December 20, 2024. The data on the causal link between CKD and CRC were pooled using risk ratio (RR), with findings reported within 95% confidence interval (CI). For MR analysis, data were synthesized from genome-wide association studies (GWAS) that concentrated on CKD and CRC in cohorts of European descent. The inverse-variance weighted (IVW) approach was utilized as the primary method for MR analysis. Results This meta-analysis encompassed 8 cohort studies involving 613,135 CKD patients and 733,068 controls. The pooled results revealed that CKD was associated with an increased risk of CRC in the total population (RR: 1.332, 95% CI 1.084–1.637, 95% prediction interval [PI] = 0.669–2.651). Subgroup analysis indicated that the association between CKD and elevated CRC risk was more pronounced in individuals younger than 50 years (RR: 2.119, 95% CI 1.205–3.725, 95% PI = 0.276–16.284) and in women (RR: 1.550, 95% CI 1.121–2.144, 95% PI = 0.594 to 4.043). Further MR analysis, using the IVW approach, showed a significant causal connection between CKD and the heightened CRC risk (odds ratio [OR]: 1.171, 95% CI 1.063–1.289, p = 0.001). Results from the sensitivity analyses provided no evidence of heterogeneity or horizontal pleiotropy in MR analysis. Conclusion Evidence from meta-analysis and MR analysis suggested that CKD may increase the risk of CRC. It remains essential to further investigate the relationship between CKD and CRC incidence across diverse ethnic populations.